Pengaruh Model Pembelajaran Write Arround Berbantuan Media Gambar Seri Digital Berbasis Canva terhadap Keterampilan Menulis Karangan Narasi pada Siswa Sekolah Dasar - Nabilah, Khairun; Nurmahanani, Indah; Rosmana, Primanita Sholihah (AS-SABIQUN, 2025)
This study aims to examine the effect of the Write Around learning model assisted by digital image media on students' narrative writing skills in elementary school. This experimental research used a pretest-posttest control group design. The subjects were two classes: the experimental class, which used the Write Around model assisted by digital image media based on Canva, and the control class, which applied the Problem-Based Learning (PBL) model. The results show that the Write Around model assisted by digital image media is effective in improving students' narrative writing skills. This is evident from the average score increase from 7.2 in the pretest to 18.3 in the posttest in the experimental class, while the control class only reached 13.6 in the posttest. Statistical tests also showed a significant difference between the experimental and control classes, with the Write Around model having a greater impact on students' writing skills. Based on these findings, it can be concluded that the use of an innovative learning model assisted by digital media, specifically Canva-based digital images, can be an effective solution to enhance students' literacy skills, particularly in narrative writing.